Optical Fiber Excitation of Fano Resonances in a Silicon Microsphere. Issue 1 (2nd January 2016) - Sabahattin Gökay, Ulaş; Zakwan, Muhammad; Demir, Abdullah; Serpengüzel, Ali
Abstract: In this article, Fano lineshape whispering gallery modes were observed in the light scattering spectrum of a silicon microsphere in near-infrared telecommunication wavelengths. A simple model is presented to explain the transition from Lorentzian lineshape to the Fano lineshape resonances with the coupled-mode theory of multiple whispering gallery modes. Polar mode spacing of 0.23 nm is observed in the spectra, which correlates well with the calculated value. The quality factor of the Lorentzian and Fano resonances are on the order of 10 5 . By using an appropriate interface design for the microsphere coupling geometries, Fano lineshape optical resonances herald novel device applications for silicon volumetric lightwave circuits.